IMPROVING STUDENTS"™ NARRATIVE TEXT WRITING THROUGH STUDENT TEAM ACHIEVEMENT DIVISION (STAD) METHOD - Kurniasari, Ratih; Regina, Regina; Bunau, Eusabinus (Journal of English Education Program, 2022)
The aim of this research is to find out how the use of Student Team Achievement Division (STAD) improves students"™ narrative text writing. This research was Classroom Action Research (CAR) which was conducted in two cycles. The research subject was XI IAI students of MAN 1 Pontianak consists of 38 students. The researcher collected the data of students"™ improvement in writing from students"™ results of writing narrative text, observation checklist, and field notes. It was found that students"™ narrative text writing improved from cycle 1 to cycle 2. The implementation of STAD improved students' skill to compose narrative text corresponding with the aspects of writing: content, organization, vocabulary, language use, and mechanics. Besides that, the students"™ teamwork and the courage to answer questions also increased due to the rewards given by the researcher. Therefore, the researcher recommends using STAD as a technique to teach writing narrative text.